Screening and identification of key microRNAs and regulatory pathways associated with the renal fibrosis process. (13th May 2022) - Li, Xiang; Dong, Zhi-Qiang; Chang, Hong; Zhou, Hong-Bing; Wang, Jia; Yang, Zhan-Jun; Qiu, Min; Bai, Wan-Fu; Shi, Song-Li
Abstract : This study analyzed the miRNA network involved in the occurrence and development of renal fibrosis in rats using transcriptomics and bioinformatics to identify novel diagnostic biomarkers and potential therapeutic targets. Abstract : Renal fibrosis (RF) is a chronic and fatal disease related to the gradual deterioration of kidney function. MicroRNAs (miRNAs) play a key role in cellular functions and several of them related to the pathogenesis of RF have been identified, although the underlying mechanisms are unclear. In order to explore the miRNAs involved in RF progression, we established a model in rats by the unilateral ureteral ligation method. The animals were randomly divided into the control group, and the 2 week, 4 week and 6 week model groups. The indices of renal function were measured using routine biochemical assays. The differentially expressed miRNAs (DE-miRNAs) between the sham-operated and modelled rats were screened, and their putative target genes were identified using the miRanda software and functionally annotated by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. The expression of transforming growth factor β1 (TGF-β1), Smad3 and Smad7 was confirmed by RT-PCR. Compared to the sham-operated group, the model groups showed a decrease in SOD activity, along with the increased renal coefficient, and higher MDA, HYP, Scr, BUN and ALB levels. In addition, TGF-β1, Smad3 and Smad7 were also upregulated in the RF groups. We identified 274 known and 11 novel DE-miRNAs in the 2 week, 114 known and 6 novel DE-miRNAs in the 4 week, and 41 known and 1 novel DE-miRNAs in the 6 week model groups. The putative target genes of these DE-miRNAs were enriched in metabolic processes, apoptosis, pyrimidine metabolism, and TNF and VEGF signalling pathways. Based on our findings, we surmise that miR-146a-3p, miR-148a-3p, miR-130a-5p, miR-362-3p and miR-122-5p are likely to be involved in the occurrence and development of RF, and miR-122-5p may play an inhibitory role. The underlying mechanisms need further investigation.